Human RecQL4 helicase plays multifaceted roles in the genomic stability of normal and cancer cells. (28th January 2018) - Mo, Dongliang; Zhao, Yongliang; Balajee, Adayabalam S.
Abstract: Human RecQ helicases that share homology with E. coli RecQ helicase play critical roles in diverse biological activities such as DNA replication, transcription, recombination and repair. Mutations in three of the five human RecQ helicases (RecQ1, WRN, BLM, RecQL4 and RecQ5) result in autosomal recessive syndromes characterized by accelerated aging symptoms and cancer incidence. Mutational inactivation of Werner ( WRN ) and Bloom ( BLM ) genes results in Werner syndrome (WS) and Bloom syndrome (BS) respectively. However, mutations in RecQL4 result in three human disorders: (I) Rothmund-Thomson syndrome (RTS), (II) RAPADILINO and (III) Baller-Gerold syndrome (BGS). Cells from WS, BS and RTS are characterized by a unique chromosomal anomaly indicating that each of the RecQ helicases performs specialized function(s) in a non-redundant manner. Elucidating the biological functions of RecQ helicases will enable us to understand not only the aging process but also to determine the cause for age-associated human diseases. Recent biochemical and molecular studies have given new insights into the multifaceted roles of RecQL4 that range from genomic stability to carcinogenesis and beyond. This review summarizes some of the existing and emerging knowledge on diverse biological functions of RecQL4 and its significance as a potential molecular target for cancer therapy. Highlights: Mutations in RecQL4 helicase results in three autosomal recessive human disorders that are characterized by premature aging features and increased cancer susceptibility. RecQL4 is aberrantly elevated in multiple human cancers. Elevated expression of RecQL4 confers survival and proliferative advantage to cancer cells. RecQL4 plays multifaceted roles in maintaining the genomic stability of nuclear and mitochondrial genomes in normal and cancer cells. RecQL4 is emerging as a prognostic/diagnostic marker for cancer and possibly a novel molecular target for improving individualized cancer therapy.